Lithospheric Flexure Controls on Geomorphology, Hydrology, and River Chemistry in the Andean Foreland Basin - Repasch, Marisa (2023)
Tectonics exerts a strong control over the morphology of Earth´s surface that is apparent in active mountain belts. In lowland areas, subtle processes like lithospheric flexure and isostatic rebound can impact Earth surface dynamics, hydrologic connectivity, and topography, suggesting that geomorphic and hydrologic analyses can shed light on underlying lithospheric properties. Here we examine the effect of lithospheric flexure on the geomorphology, hydrology, and river water chemistry of the Rio Bermejo fluvial system in the east Andean foreland basin of northern Argentina. Results show that proximal to the mountain front, foredeep basin subsidence causes sedimentation along a braided channel belt that is superelevated relative to the surrounding flood basin. During floods, water flows from the superelevated channel into the groundwater reservoir, causing a net loss of discharge with distance downstream. Further downstream, forebulge uplift forces channel narrowing, high lateral migration rates, and incision up to 13 m into older river deposits. This incision locally allows groundwater flow into the river, causing a ∼20% increase in river solute load. Groundwater emerges from the forebulge into the backbulge, predominantly as spring-fed channels. Here, channel migration rates decrease, suggesting a switch from net uplift to subsidence that reduces the depth to the groundwater table. This analysis shows that subtle lithospheric flexure can have significant effects on river channel morphology that determine hydrologic flow paths, and ultimately influence geochemical and ecological patterns. We suggest that these effects may elucidate lithospheric properties that are otherwise inferred from bulk geophysical observations.